2019
DOI: 10.1097/md.0000000000015193
|View full text |Cite
|
Sign up to set email alerts
|

First trimester Doppler velocimetry of the uterine artery ipsilateral to the placenta improves ability to predict early-onset preeclampsia

Abstract: This study sought to investigate the effects of placental laterality on the measurements of uterine artery (UtA) Doppler velocimetry and their application in predicting early-onset preeclampsia (PE). We conducted a prospective cohort study on all women with singleton, uncomplicated pregnancies scheduled for first-trimester nuchal translucency at our institution. Pulsatility index (PI) for both UtAs was measured by Doppler velocimetry, and placental laterality was determined. Additionally, pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, an in-vivo assessment tool that can reliably quantify impaired SAR has not been developed. Although uterine artery flow resistance is currently used as a proxy marker for impaired placentation, its value in the first and second trimesters as a standalone test is limited [4][5][6] . Histological studies show clearly that extensively remodeled spiral arteries have a thin wall that accommodates increased blood flow, whereas poorly remodeled vessels retain a thickened wall and narrow lumen 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, an in-vivo assessment tool that can reliably quantify impaired SAR has not been developed. Although uterine artery flow resistance is currently used as a proxy marker for impaired placentation, its value in the first and second trimesters as a standalone test is limited [4][5][6] . Histological studies show clearly that extensively remodeled spiral arteries have a thin wall that accommodates increased blood flow, whereas poorly remodeled vessels retain a thickened wall and narrow lumen 7 .…”
Section: Introductionmentioning
confidence: 99%
“…If maternal body mass index (BMI) is too high, the uterine artery PI (UtA-PI) will be less ( 1 ). Besides, UtA-PI of the placental side is lower than that of the non-placental side ( 24 ).…”
Section: Uad In a Normal Pregnancymentioning
confidence: 82%
“…If maternal body mass index (BMI) is too high, the uterine artery PI (UtA-PI) will be less (1). Besides, UtA-PI of the placental side is lower than that of the non-placental side (24). "Notching" is a relatively common characteristic that appears during the early stages of 46-64% of normal pregnancies (1).…”
Section: Uad In a Normal Pregnancymentioning
confidence: 99%
“…Studies have reported that placenta localization is effective in uterine artery Doppler, and there is an increase in the uterine artery Doppler PI of the contralateral side of the placenta. 41,42 Oloyede and Iketubosin reported that left uterine artery Doppler values were higher than right uterine artery Doppler values in normal pregnancies. They also stated that this increase was evident in patients with placental disorders.…”
Section: Discussionmentioning
confidence: 98%